Predictive values of egg‐specific IgE by two commonly used assay systems for the diagnosis of egg allergy in young children: a prospective multicenter study. Issue 10 (13th July 2016) - Furuya, K.; Nagao, M.; Sato, Y.; Ito, S.; Fujisawa, T.; ,
Abstract: Background: Specific IgE (sIgE) is often used to predict oral food challenge (OFC) outcomes in food allergy, but interpretation of the results may vary depending on the assay method employed and the patient population tested. The aim of this study was to use two commercial assay systems to determine egg‐sIgE values predictive of allergy within the most common populations treated at pediatric clinics. Methods: In a multicenter prospective study, 433 children with suspected or confirmed egg allergy underwent oral challenge (OFC) using cooked egg (CE) and raw egg (RE) powders to diagnose either true allergy in 1‐year‐old (group A, n = 220) or tolerance in 2‐ to 6‐year‐old (group B, n = 213). Egg white (EW)‐ and ovomucoid (OM)‐sIgE values were measured using the ImmunoCAP ® sIgE (ImmunoCAP) and the IMMULITE ® 2000 3 gAllergy ™ (3gAllergy) systems. Children were recruited from six primary care clinics and 18 hospitals in Japan. Results: Receiver‐operating characteristic (ROC) curve analysis yielded similar areas under the curve (AUC) for the two assays (0.7–0.8). The optimal cutoff values and the probability curves (PCs) of the sIgE by the two assays to predict CE and RE OFC outcomes were determined for both groups. Values for 3gAllergy were higher than for ImmunoCAP; however, correlation of sIgE and predicted probability calculated by PCs were strong between the two methods. Conclusions: Cutoff values and PCs for egg‐sIgE established using both ImmunoCAP and 3gAllergy may be useful for predicting egg allergy in early childhood patient populations.